1988
DOI: 10.1128/aem.54.10.2510-2514.1988
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of ruminal fermentation characteristics and microbial populations in bison and cattle

Abstract: Ruminal microbial populations, fermentation characteristics, digestibility, and liquid flow rates in two ruminally cannulated bison and two ruminally cannulated Hereford steers fed a prairie hay diet were compared. No significant differences in anaerobic bacterial counts, volatile fatty acid concentrations, or ruminal pHs were evident between bison and cattle. Also, no significant differences in neutral detergent fiber digestibility, indigestible fiber retention time, or intake were detected between bison and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…Extended in vivo digesta retention time in sites of microbial fermentation may permit greater digestion of forage (Schafer et al 1978). While Schafer et al ( 1978) found that mean digesta retention time was 18% longer in bison than cattle, Towne et al (1988) found no differences in mean retention time. Because it is unclear whether bison actually exhibit greater mean digesta retention time than cattle we feel that 48-h in vitro dry matter digestibility (IVDMD) is an appropriate comparative measure of digestibility.…”
Section: Diet Qualitymentioning
confidence: 93%
See 4 more Smart Citations
“…Extended in vivo digesta retention time in sites of microbial fermentation may permit greater digestion of forage (Schafer et al 1978). While Schafer et al ( 1978) found that mean digesta retention time was 18% longer in bison than cattle, Towne et al (1988) found no differences in mean retention time. Because it is unclear whether bison actually exhibit greater mean digesta retention time than cattle we feel that 48-h in vitro dry matter digestibility (IVDMD) is an appropriate comparative measure of digestibility.…”
Section: Diet Qualitymentioning
confidence: 93%
“…Dietary IVDMD generally remained elevated during the first half of the summer and then declined to a fairly constant level during the second half of the growing season. Towne et al (1988) have shown that bison average greater ruminal ammonia nitrogen concentrations, more total ciliate protozoal counts, and higher ciliate cell volume than cattle, while the percentages of protozoans and cellulolytic bacteria in the bison rumen are different from those of cattle (Varel and Dehority 1989). Bison exhibit a Type B ruminal protozoa population, whereas cattle exhibit a Type A or mixed A-B protozoal population (Towne et al 1988).…”
Section: Forage Digestibility and Diet Qualitymentioning
confidence: 99%
See 3 more Smart Citations